Collective action in watershed management: Experiences from the Andean hillsides - Ravnborg, Helle Munk; Guerrero, M.P. (Springer, 1999)
Watersheds constitute a special case of multiple-use common pool resources (CPRs). In a textual sense, watersheds tend to be mosaics of privately owned and managed patches of land. At the same time, however, watersheds are also ecosystems in which multiple resources and people interact through an infinity of bio-physical processes. Through such interaction, new watershed-level qualities emerge that, together with other factors, condition watershed users' continued resource use and access. In this perspective, watersheds become common-pool resources. Hence, watershed users do not only manage their individual plots, crops, forests, etc., knowingly or not, they manage landscape patterns and bio-physical processes that transcend their private property. In this context, drawing on experiences gained through participatory action research in a micro-watershed in the Andean hillsides of southern Colombia, this paper describes a process aimed at fostering collective watershed management. The paper illustrates the importance of platforms as a mechanism for negotiating and coordinating collective action by multiple users and discusses the issues of representation on such platforms as well as the importance of third party facilitation.